Quality of antenatal care and associated factors among pregnant women attending government hospitals in Sidama Region, Southern Ethiopia - Assefa Philipos Kare; Amelo Bolka Gujo; Nigussie Yohanes Yote (SAGE Open Medicine, 2021)
Background: Good-quality antenatal care improves maternal health in the least developed countries. This study was aimed at assessing the quality of antenatal care and associated factors among pregnant women attending hospitals in the Sidama Region, Southern Ethiopia. Method: A facility-based cross-sectional study was conducted from 1 February to 30 April 2020 among 372 pregnant women. A two-stage sampling technique—the first stage, selection of health facilities; the second stage, selection of respondents—was used. Trained data collectors administered exit interviews. Data were entered into EPI Info 7 and analyzed using IBM SPSS version 25. Quality of care was assessed using a validated questionnaire containing 68 attributes of quality. Good quality of care was determined by the proportion of respondents who scored ⩾80% of 68 variables. Bivariable and multivariable logistic regressions were used in the analysis. The outputs were presented using an adjusted odds ratio with 95% confidence intervals. Results: This study revealed that 41.2% (95% confidence interval: 36.2%–46.2%) of pregnant women had received good-quality antenatal care. Increased odds of the utilization of quality antenatal care were observed among women who lived in urban areas (adjusted odds ratio = 4.32, 95% confidence interval: 2.58–7.21), attained primary education and more (adjusted odds ratio = 2.68, 95% confidence interval: 1.60–4.48), earned a monthly income >3000 Ethiopia Birr (US$93.3) (adjusted odds ratio = 3.86, 95% confidence interval: 2.28–6.51), and visited hospitals for antenatal care ⩾4 times (adjusted odds ratio = 3.68, 95% confidence interval: 2.21–6.10). Conclusions: The proportion of women who received good-quality antenatal care was low. Good quality care was associated with residence, education status, income level, and frequency of antenatal care visits. Training care providers, strengthening counseling, and promoting women’s economic empowerment to improve the utilization of quality antenatal care are recommended.